CO2 Emissions in ASEAN-5: The Role of Labor, Investment, Inflation, Exchange Rate, and Economic Growth - Lubis, Sanny F.; Silvia, Vivi; Dawood, Taufiq Carnegie (Heca Sentra Analitika, 2025)
Labor and investment can raise emissions in the short term but may reduce them in the long term if energy efficiency improves. Inflation influences emissions through changes in energy prices and production costs. The exchange rate affects emissions by altering the cost of imported energy and green technologies. Economic growth generally increases emissions, especially in early development stages, as described by the Environmental Kuznets Curve (EKC) hypothesis. Given these linkages, this study examines the effects of labor, investment, inflation, exchange rate, and economic growth on CO2 emissions in ASEAN-5 countries. To ensure robust findings, the study uses the Autoregressive Distributed Lag (ARDL) model and applies Dynamic Ordinary Least Squares (DOLS) and Fully Modified Ordinary Least Squares (FMOLS) for dynamic estimations. Results show that labor, exchange rate, and economic growth do not significantly impact CO2 emissions in the short term. However, investment and inflation have significant positive effects, indicating they contribute to short-term emission increases. In the long term, labor, investment, and inflation significantly reduce emissions, while the exchange rate remains insignificant. Economic growth, however, significantly increases emissions over time. This suggests that without strong environmental policies, continued economic expansion may lead to higher emissions. Overall, the findings highlight that structural factors like investment and economic growth are crucial in shaping CO2 emissions. Policies such as carbon taxes or emissions trading systems can help internalize the environmental costs of emissions, encouraging a shift to cleaner energy and reducing fossil fuel dependence.